2017
DOI: 10.1073/pnas.1711201114
|View full text |Cite
|
Sign up to set email alerts
|

Permeability transition in human mitochondria persists in the absence of peripheral stalk subunits of ATP synthase

Abstract: The opening of a nonspecific channel, known as the permeability transition pore (PTP), in the inner membranes of mitochondria can be triggered by calcium ions, leading to swelling of the organelle, disruption of the inner membrane and ATP synthesis, and cell death. Pore opening can be inhibited by cyclosporin A mediated via cyclophilin D. It has been proposed that the pore is associated with the dimeric ATP synthase and the oligomycin sensitivity conferral protein (OSCP), a component of the enzyme's peripheral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
171
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(180 citation statements)
references
References 44 publications
9
171
0
Order By: Relevance
“…This observation is important because it demonstrates that lack of swelling cannot be explained by ultrastructural differences in cristae and matrix morphology. As recently noted [47] these data are reminiscent of the effects of deletion of subunits b and OSCP in human cells [46] and suggest that the size of the channel resulting from deletion of the dimerization subunits is close to the exclusion limit of sucrose. Consistently, electron microscopy images revealed that mitochondria of ΔeΔg mutants still possess a dense matrix after PTP opening, while swelling occurred after the addition of Alamethicin (Fig.…”
Section: Ptp Size Is Affected By Deletion Of E and G Subunitssupporting
confidence: 57%
See 3 more Smart Citations
“…This observation is important because it demonstrates that lack of swelling cannot be explained by ultrastructural differences in cristae and matrix morphology. As recently noted [47] these data are reminiscent of the effects of deletion of subunits b and OSCP in human cells [46] and suggest that the size of the channel resulting from deletion of the dimerization subunits is close to the exclusion limit of sucrose. Consistently, electron microscopy images revealed that mitochondria of ΔeΔg mutants still possess a dense matrix after PTP opening, while swelling occurred after the addition of Alamethicin (Fig.…”
Section: Ptp Size Is Affected By Deletion Of E and G Subunitssupporting
confidence: 57%
“…Since pore size is affected by lack of lateral stalk subunits [46] we analyzed PTP-dependent swelling in mitochondria devoid of e and g subunits. We loaded mitochondria with a Ca 2+ bolus of the same size and triggered PTP opening with the SH reagent copper-o-phenantroline Cu(OP) 2 release readily ensued, and its rate was not substantially affected in any of the mutants (Fig.…”
Section: Ptp Size Is Affected By Deletion Of E and G Subunitsmentioning
confidence: 99%
See 2 more Smart Citations
“…In both cases (a) a vestigial F‐ATP synthase was assembled that additionally lacked several subunits of the peripheral stalk and (b) a severe respiratory defect was present, with basal rates of about 20% of those of parental cells, lack of sensitivity to oligomycin and negligible stimulation by uncoupler. Consistently, these cell lines also displayed major alterations in respiratory chain assembly, with virtually no mature complex I, decreased complex III and lower levels of complex IV . Even more surprisingly given the absence of complex I, also in this case after cell permeabilization with digitonin mitochondria incubated with glutamate and malate accumulated Ca 2+ ; further, they underwent spontaneous release after the same Ca 2+ load and responded to CsA just as their parental, respiratory‐competent counterpart .…”
Section: Evidence That F‐atp Synthase Does Not Generate the Ptpmentioning
confidence: 66%